Ideologia e ensino-aprendizagem de inglês na escola pública - Fernandes, Paula Telles da Costa (2011)
This paper aims to examine the ideological aspects related to teaching-learning English as a foreign language at a public school. It is intended to contribute to a better understanding of such aspects, which are raised both in the teacher s discourse and in his/her classroom practices. The concept of ideology as applied in this paper stems from Bakhtin & The Circle, and refers to ideology as a way in which one views the world. However, while embracing Bakhtin & The Circle s concept of ideology as essentially social and historical, this paper is also theoretically grounded in Apple s perspectives about ideology and education as well as Bakhtin/Voloshinov s works on ideological sign. The most significant common ground between these theories lies on their identification with Marxist ideas. Therefore, historical dialectical Marxism underlies the theoretical framework of all these writers. This research was carried out on a critical basis (Kincheloe & Mc Laren) within a qualitative paradigm, and was based on classes and reflective talks with two English teachers from a São Paulo State public school. Data were gathered throughout seven months (from May to November, 2009) and showed a clear relationship between the teacher s ideology and his/her classroom practices. The analysis provided in this paper brings forth the discourse topics that better explain the core issue of this research, i.e. public school English teaching-learning based on reading and writing practices allied with a great emphasis on translating words and sentences that are ultimately detached from a linguistic situational context. The results suggest that there is a strong relationship between the teacher s ideology and his/her classroom practices while teaching English at a public school